INFLUENCE OF MAXILLARY FRENUM IN THE DEVELOPMENT OF DENTAL CARIES IN PRIMARY ANTERIOR TEETH - P.S. SUBIKSHA; DR. G. DEEPA (International Journal of Pharma and Bio Sciences, 2016)
The aim of the study is to evaluate the influence of maxillary frenal influence on the development of dental caries in primary anterior teeth. BACKGROUND: The maxillary labial frenum is a fold of the mucous membrane connecting the lip to the alveolar process.The maxillary frenum often attaches to the centre of the upper lip and between the upper two front teeth. Incidences of improper attachment of the frenum are a common problem occurring in children than in adults. This study involves 200 healthy patients aged between 3-6yrs who have come to Saveetha dental college for dental checkup. This is a questionnaire based study on the type of frenal attachment and clinical examination of presence and extent of caries in primary anterior teeth. RESULT It is seen in this study that 125 out of 200 children had dental caries in their primary anterior teeth. The type of frenum attachment which is associated with the development of caries in anterior teeth is type 3. In children an abnormal attachment of maxillary frenum has the potential to become a significant factor in contributing to caries formation on the maxillary anterior teeth. This may be due to the inability of infants to remove residual milk from the area between the lip and facial surfaces of the maxillary central and lateral incisors at the completion of nursing.